SEX GUILT IN ADOLESCENTS: STUDYING SOME RELATED FACTORS - Ortega, Virgilio; Ojeda, Pilar; Sutil, Francisca; Sierra, Juan Carlos (Anales de Psicología / Annals of Psychology, 2005)
The aim of this study has been to identify the presence of sexual myths among adolescents, as well as to determine the level of sex guilt they experience according to many sociodemographic, behavioral and cognitive criterias. A sample of 174 students with age ranging from 14 to 17 years completed the Exploratory Battery of Sexuality (BES-III. Attitudes), sex guilt scale taken from the Mosher Guilt Inventory-Revised (RMGI), the Negative Attitudes toward Masturbation Inventory (NAMI), the Sex Fantasy Questionnaire (SFQ), and the Sexual Opinion Survey (SOS). It was found that the presence of certain sexual myths was related to the individual’s sex and to population size by place of residence. Negative attitudes toward masturbation and masturbatory abstinence, unconventional sex, and exploratory sexual fantasies were shown linked to a higher sex guilt; however, practicing masturbation, having sex with a single partner, erotophilic attitudes, and intimate fantasies revealed lower sex guilt. Implications of these results are discussed in relation to the necessity of sex education for teenagers, also the coercive role that some social devices seem to play on this topic.